Early Decline of Androgen Levels in Healthy Adult Men: An Effect of Aging Per Se? A Prospective Cohort Study - Banica, Thiberiu; Verroken, Charlotte; Reyns, Tim; Mahmoud, Ahmed; T’Sjoen, Guy; Fiers, Tom; Kaufman, Jean-Marc; Lapauw, Bruno (The journal of clinical endocrinology and metabolism, 2021)
Abstract Context Androgen levels have been shown to decline in aging men. However, there is no consensus on the effect of aging, (changes in) body mass index (BMI), lifestyle factors, and intercurrent disease. Objective Investigating longitudinal changes in serum androgen levels in healthy men in relation to body composition, lifestyle factors, and intercurrent disease. Design, Setting, and Participants Longitudinal, population-based sibling pair study at a university research center. 999 healthy men aged 24 to 46 years of whom 691 were reevaluated after a mean period of 12 years. Main outcome measures Serum SHBG, LH, and FSH levels measured using immuno-assays. Testosterone (T), estradiol (E2), dihydro-testosterone (DHT), and androstenedione (Adione) measured using liquid chromatography-tandem mass spectometry, free T calculated (cFT). Results Baseline age was 34 ± 6 years. Mean BMI increased by 1.19 kg/m2, T levels decreased by 14.2% (20.8 nmol/L vs. 17.8 nmol/L), cFT by 19.1% (392 pmol/L vs. 317 pmol/L), DHT by 15.6% (1.5 nmol/L vs.1.3 nmol/L), and Adione by 10.7% (3.7 nmol/L vs. 3.3 nmol/L; all P < 0.001). E2 did not change over time. SHBG increased by 3.0% (39.8 nmol/L vs. 41.0 nmol/L), LH by 5.8% (4.6 U/L vs. 4.9 U/L) and FSH by 14.7% (4.3 U/L vs. 5.1 U/L) (all P < 0.001). For T, cFT, DHT, Adione, and SHBG, these longitudinal changes persisted after adjustment for confounders (all P < 0.001). Conclusion Serum androgen levels start declining early during adult life and independently from changes in BMI and other lifestyle factors, suggesting that aging per se leads to an altered sex steroid status. Given the concurrent rise in gonadotropin levels, the decline in androgen status most likely arises from primary decrease in testicular function.